Monetary and macroprudential policy: The multiplier effects of cooperation - Federico Bassi; Andrea Boitani (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2021)
A BMW model is augmented with a credit market affected by banks' balance sheet and used to assess the dynamic performance of an economy in the face of demand and financial shocks under different assumptions about the interactions between monetary and macroprudential policy. We show that the regulatory bank's capital requirement has a multiplier effect that interferes with monetary policy, thus influencing the credit market and the output gap, and this multiplier effect varies according to the institutional arrangements in which macroprudential and monetary policies are embedded. In particular, we find that cooperation between monetary policy and macroprudential policy delivers the best overall stabilization outcomes in the face of both negative demand and bank equity shocks, if such shocks are not highly persistent. As shock persistence increases, non-cooperation or a simple leaning against the wind monetary policy outperform cooperation. However, adding countercyclical capital buffers in the macroprudential toolkit reinstates the original ranking of institutional arrangements with cooperation dominating overall.
Keywords: E44; E52; E58; E61; G21; G28; 330; Financial Frictions; Monetary Policy; Macroprudential Policy; Policy Coordination